Endoscopic Step Up: A Colon-Sparing Alternative to Colectomy to Improve Outcomes and Reduce Costs for Patients With Advanced Neoplastic Polyps. Issue 6 (June 2020) - Cohan, Jessica N.; Donahue, Colleen; Pantel, Haddon J.; Ricciardi, Rocco; Kleiman, David A.; Read, Thomas E.; Marcello, Peter W.
Abstract : BACKGROUND: The optimal strategy for colonic polyps not amenable to traditional endoscopic polypectomy is unknown. Endoscopic step up is a promising strategy for definitive treatment. OBJECTIVE: The purpose of this study was to determine whether endoscopic step up leads to improved outcomes and decreased costs compared with planned colectomy for endoscopically unresectable colon polyps. DESIGN: This was a retrospective review of a prospective database. SETTING: The study was conducted at a tertiary referral center. PATIENTS: Consecutive patients referred for endoscopically unresectable colon polyps 15 to 50 mm in size were included. INTERVENTIONS: Patients underwent planned colectomy or endoscopic step up at the surgeon's discretion. Endoscopic step up began with diagnostic colonoscopy in the operating room. If the polyp was amenable to endoscopic removal, endoscopic mucosal resection or endoscopic submucosal dissection was performed with progression to combined endoscopic–laparoscopic surgery or laparoscopic colectomy, as indicated. MAIN OUTCOME MEASURES: The primary outcome was 30-day adverse events. We also examined length of stay, hospital charges, insurer payments, and polyp recurrence. RESULTS: A total of 52 patients underwent planned colectomy (48 laparoscopic), and 38 underwent endoscopic step up (28 endoscopic mucosal resection, 2 endoscopic submucosal dissection, 6 combined endoscopic-laparoscopic surgery, and 2 colectomy). Compared with planned colectomy, endoscopic step-up patients had fewer complications (13% vs 33%; p = 0.03) and shorter length of stay (median, 0 vs 4 d; p < 0.001). There was 1 readmission in the endoscopic step-up group and 5 in the planned colectomy group. Endoscopic step-up patients had lower hospital costs ($4790 vs $13, 004; p < 0.001) and insurer payments ($2431 vs $19, 951; p < 0.001). One-year polyp recurrence-free survival was 84% (95% CI, 67%–93%) in endoscopic step-up patients. All of the recurrences were benign, <1 cm, and managed endoscopically. LIMITATIONS: The study was limited by its nonrandomized design and short follow-up. CONCLUSIONS: An endoscopic step-up approach to colon polyps is associated with less morbidity, decreased healthcare costs, and colon preservation in 95% of patients. Additional studies are needed to evaluate long-term quality of life and polyp recurrence in this group. See Video Abstract at http://links.lww.com/DCR/B188 . Endoscopic Step Up: Una Alternativa a Colectomía Para Preservación de Colon Con los Propósitos de Mejorar Resultados y Reducir Costos en Pacientes Con Pólipos Neoplásicos Avanzados: ANTECEDENTES: Se desconoce la estrategia óptima para los pólipos de colon no susceptibles a la polipectomia endoscópica tradicional. Endoscopic Step Up es una estrategia prometedora para el tratamiento definitivo. OBJETIVO: Determinar si Endoscopic Step Up produce mejores resultados y menores costos en comparación con la colectomía programada para pólipos de colon endoscópicamente no resecables. DISEÑO: Revisión retrospectiva de una base de datos prospectiva. ENTORNO CLINICO: Centro de referencia de tercer nivel. PACIENTES: Pacientes consecutivos remitidos para pólipos de colon endoscópicamente irresecables de tamaño 15-50 mm. INTERVENCIONES: Los pacientes se sometieron a colectomía programada o Endoscópico Step Up a discreción del cirujano. Endoscopic Step Up comenzó con una colonoscopia diagnóstica en el quirófano. Si el pólipo era susceptible de extirpación endoscópica, la resección endoscópica de la mucosa o la disección submucosa endoscópica se realizaba con progresión a cirugía endoscópica-laparoscópica combinada o colectomía laparoscópica, según a cosnideraciones clínicas en el transoperatorio. PRINCIPALES MEDIDAS DE VALORACION: El resultado primario fue los eventos adversos a 30 días. Duración de la estadía hospitalaria, los cargos hospitalarios, los pagos de las aseguradoras y la recurrencia de pólipos también fueron examinados. RESULTADOS: Un total de 52 pacientes se sometieron a colectomía programada (48 laparoscópicas) y 38 se sometieron a Endoscopic Step Up (28 resección endoscópica de la mucosa, 2 disección submucosa endoscópica, 6 cirugía endoscópica-laparoscópica combinada y 2 colectomía). En comparación con la colectomía programada los pacientes endoscópicos Step Up tuvieron menos complicaciones (13% versus 33%, p = 0.03) y una estadía hospitalaria más corta (mediana 0 versus 4 días, p <0.001). Hubo 1 reingreso hospitalario en el grupo Endoscopic Step Up y 5 en el grupo de colectomía programada. Los pacientes endoscópicos Step Up tuvieron costos hospitalarios más bajos ($ 4, 790 versus $ 13, 004, p <0, 001) y pagos de la aseguradora ($ 2, 431 versus $ 19, 951, p <0, 001). La supervivencia libre de recurrencia de pólipos a un año fue del 84% (IC 95% 67-93) en pacientes endoscópicos Step Up. Todas las recurrencias fueron benignas, <1 cm, y manejadas endoscópicamente. LIMITACIONES: Diseño no aleatorizado y seguimiento corto. CONCLUSIONES: El abordaje endoscópico Step Up para pólipos de colon se asocia con menos morbilidad, disminución de los costos de atención médica y preservación del colon en el 95% de los pacientes. Se ocupan más estudios para evaluar la calidad de vida a largo plazo y la recurrencia de pólipos en este grupo. Consulte Video Resumen en http://links.lww.com/DCR/B188 . ( Traducción—Dr Adrián Ortega Robles)